Memories that will not die – Roberta Carreri in "Flowers for Torgeir" - Annelis Kuhlmann (Il castello di Elsinore, 2022)
This essay charts Roberta Carreri’s performance Flowers for Torgeir, a solo performance, dedicated to her partner in life and art. Torgeir Wethal died in 2010. The performance is a co-creation together with the German-Italian video-artist, Stefano Di Buduo and the Danish dramaturg, Anne Middelboe Christensen. Flowers for Torgeir had its official premiere on 4 September 2020. Through the prism of the diapason between light and darkness, the essay throws another light on the performance Flowers for Torgeir. It is perceived as an interweaving of not only a staged professional biography as a theatrical scope of life but also performing memories of a co-creativity in the performance history of Odin Teatret. Torgeir Wethal was cofounder of Odin Teatret together with the theatre director, Eugenio Barba in Oslo in 1964.